Neue Behandlungsoptionen bei Gliomen = New treatment options for gliomas - Wick, Wolfgang (Der Onkologe, 2019)
BackgroundPatients with gliomas in molecularly defined subgroups (isocitrate dehydrogenase, IDH mutation, 1p/19q codeletion) already benefit now from standard treatments. The O6-methylguanine DNA-methyltransferase (MGMT) is the only relevant biomarker for treatment decisions for or against alkylating chemotherapy.PurposeIn the present review article new concepts of immunotherapy and targeted approaches as well as treatment with electrical fields for gliomas are discussed.ResultsIn recent years there have been efforts to develop study concepts with molecular targeted treatment for patients with gliomas harboring IDH mutations, endothelial growth factor receptor (EGFR) overexpression, EGFRv3 expression and also other defined molecular alterations in tumor tissue. Current treatment studies transfer these to studies involving single biomarkers in so-called modern umbrella designs. In these umbrella concepts a single disease entity is treated in different study groups with molecular targeted treatments based on molecular biomarker tests. Key outcomes of these trials are not only patients who benefit but also information on sensitivity or resistance mechanisms of the examined treatments. Similar trials are being designed for immunotherapies with variable approaches involving checkpoint inhibition on the one side and different vaccination approaches including the use of chimeric antigen receptor (CAR) cells on the other.ConclusionAlternating electrical fields are a therapeutic option available for patients with newly diagnosed glioblastoma after successful completion of chemoradiation.
Gesehen am 22.07.2019